(untitled) (Research, Society and Development, 2023)
Introduction: Borderline Personality Disorder (BPD) presents instability in interpersonal relationships, affections and self-image, with impulsivity being a hallmark of this disorder. The diagnosis of BPD is performed according to the criteria defined by the DSM-5 and there is evidence that early diagnosis and treatment are beneficial, especially in terms of improving the psychosocial functioning of patients. Objective: It aims to analyze the importance of early diagnosis of Borderline Personality Disorder. Methodology: The following databases were used: PUBMED, LILACS and SCIELO. The selected descriptors were found in the Health Sciences Descriptors dictionary (DeCS) and Medical Subject Heading Terms (MeSH), with the formulas “Borderline personality disorder” AND “Early diagnosis”. Articles from 2018 to 2022 were used. Result: The database search resulted in 123 studies, 11 of which were analyzed and included in this review. There was a strong incidence of this disorder in female patients, in addition to its association with other disorders, such as anxiety and depression. Added to this, it was identified an increase in direct and indirect costs in patients with BPD and that there is the possibility of online screening of these patients, favoring early identification and minimization of costs and damage to quality of life. Conclusion: The present study shows that the discovery of BPD prevents not only the worsening of symptoms in the late phase, but also avoids fatal psychopathological outcomes, high public health costs and damage to the individual’s socio-emotional, family and professional life.